Management of esophageal varices with sclerotherapy. Preliminary report (Colombia Medica, 1987)
Endoscopic sclerotherapy is a new method for acute and long-term control of variceal bleeding of the esophagus. Initial experiences with the method at the Hospital Universitario del Valle, Cali, Colombia, including indications, technique, results, and complications, are presented.